A productive immunocompetent mouse model of cryptosporidiosis with long oocyst shedding duration for immunological studies. Issue 5 (May 2022) - He, Xi; Huang, Wanyi; Sun, Lianbei; Hou, Tianyi; Wan, Zhuowei; Li, Na; Guo, Yaqiong; Kváč, Martin; Xiao, Lihua; Feng, Yaoyu
Highlights: An immunocompetent mouse model of cryptosporidiosis is established. The isolate has low high infectivity and induce intensive and long oocyst shedding. It induces strong immune responses but down-regulates the expression of α-defensins. It has unique sequences in subtelomeric genes encoding invasion-related proteins. The model is useful in studies of pathogen biology and immune responses. Abstract: Objectives: Studies on the pathogenesis and immune responses of Cryptosporidium infection and development of drugs and vaccines use mostly immunocompromised mouse models. In this study, we establish an immunocompetent mouse model of cryptosporidiosis with high intensity and long duration of infection. Methods: We have obtained a Cryptosporidium tyzzeri isolate from laboratory mice, and infect adult C57BL/6 J mice experimentally with the isolate for determinations of infectivity, infection patterns, pathological changes, and transcriptomic responses. Results: The isolate has an ID50 of 5.2 oocysts, with oocyst shedding lasting at high levels for >2 months. The oocyst shedding is boosted by immunosuppression of animals and suppressed by paromomycin treatment. The isolate induces strong inflammatory and acquired immune responses, but down-regulates the expression of α-defensins in epithelium. Comparative genomics analysis has revealed significant sequence differences from other isolates in subtelomeric genes. The down-regulation of the expression of α-defensins may be responsible for the high-intensity and long-lasting infection in this animal model. Conclusions: The immunocompetent mouse model of cryptosporidiosis developed has the advantages of high oocyst shedding intensity and long oocyst shedding duration. It provides an effective mechanism for the propagation of Cryptosporidium, evaluations of potential therapeutics, and studies of pathogen biology and immune responses.